Improving Healthcare Through Advocacy : a Guide for the Health and Helping Professions. - Jansson, Bruce S. (John Wiley & Sons, Inc., 2010)
Praise forImproving Healthcare Through AdvocacyA Guide for the Health and Helping Professions ""Bruce Jansson's thoughtful and innovative book will appeal to students in social work, nursing, and public health as well as those working in the health field of practice. The case examples are extraordinary, and Jansson provides the ideas, context, and theoretical base for readers to acquire the skills of advocacy in healthcare. This is by far the best advocacy book I have seen.""--Gary Rosenberg, PhD Director, Division of Social Work and Behavioral S.